ОБРАЗОВНАТА ПОНУДА И ИНКЛУЗИВНОСТА ВО СФЕРАТА НА НЕФОРМАЛНОТО ОБРАЗОВАНИЕ НА ВОЗРАСНИ (Годишен зборник на Филозофски факултет - Скопје, 2020)
Profound changes in requirements and demands of new skills and competencesin the field of labour, which are preconditioned by significant technological development,changing economies, social and political establishments, place educational systemsthroughout the world (especially vocational education and training and adulteducation) ahead of a major challenge. – How to enable individuals to gain the skillsand competences needed for the labour market of the future?Accomplishing this ambitious goal means that it is necessary to change the oldparadigm of “job for a life time” to the new paradigm “learning throughout life” or “lifelonglearning”. Non-formal education in the context of lifelong learning concept isone of the paths that ensures equal opportunities for obtaining relevant skills, attitudesand competences among individuals. It is compensating the disadvantages of the formaleducation system which adapts too slowly to the socio-economic changes and is characterizedwith conservatism leading to inertia of the societies themselves.This paper tends to present educational offer and inclusion in non-formal adulteducation area, analysing the educational programme offer on one hand, and inclusivenessof the process of non-formal education on other hand. Results will point out thegood practices, as well as the challenges that will need to be addressed urgently in orderto accomplish the goal of inclusion and equity in the context of lifelong learning concept.
Keywords: НЕФОРМАЛНО ОБРАЗОВАНИЕ; ПАЗАР НА ТРУД; ИНКЛУЗИЈА